Psychosocial Responses to Emergency Situations: A Social Work Perspective on Crisis Intervention and Mental Health Support (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Emergency situations such as natural disasters, armed conflicts, pandemics, and large-scale displacement significantly disrupt individuals, families, and communities, often leading to profound psychosocial distress. Events like COVID-19 pandemic and catastrophic disasters such as Hurricane Katrina have demonstrated how crises can intensify anxiety, grief, trauma, social isolation, and economic instability. Vulnerable populations—including children, older adults, people with disabilities, and marginalized communities—are disproportionately affected due to pre-existing social and structural inequalities. Psychosocial responses to emergencies commonly include acute stress reactions, post-traumatic stress symptoms, depression, substance misuse, and disruptions in social functioning.Social workers play a critical role in mitigating these impacts through crisis intervention, advocacy, case management, and the coordination of community resources. Guided by frameworks such as Psychological First Aid (PFA), trauma-informed care, and strengths-based practice, social workers provide immediate emotional stabilization, risk assessment, and linkage to essential services such as shelter, healthcare, and financial assistance. In addition to short-term interventions, social workers contribute to long-term recovery by promoting resilience, facilitating support groups, strengthening family systems, and advocating for equitable policies that address systemic barriers.This review examines common psychosocial responses to emergencies and highlights evidence-based social work interventions designed to support mental health and community recovery. It emphasizes the importance of culturally responsive, community-centered approaches that prioritize empowerment, collaboration, and social justice. Strengthening integrated mental health systems and expanding access to psychosocial services are essential to building resilient communities capable of adapting to future crises.